Using game-based compensatory strategies in non-starter soccer players: analyzing the impact on physical fitness development - Liu, T.; Li, M.; Pu, X. (Journal of Sports Science & Medicine, 2025)
The purpose of this study was to compare the effects of small-sided game-based compensatory strategies (CS) versus non-compensatory (NCS) strategies on the aerobic and repeated sprint ability development of non-starter soccer players. A controlled crossover experimental design was used, consisting of two 4-week phases separated by a 2-week washout period. Nineteen male non-starter soccer players (age: 18.1 ± 0.7 years) participated in the study. Each player experienced both an NCS and a specific CS, the latter involving six 3-minute bouts of 2v2 small-sided games performed the day after the match. CS indicates that additional training was introduced to compensate for the lack of playing time. This intervention was applied to players who either did not participate in the match or played less than 15 minutes. Physical fitness was assessed using the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT) and the Running-Based Anaerobic Sprint Test (RSAmean). Significant interactions were found for YYIRT (p < 0.001, np2 = 0.587, large effects) and RSAmean (p < 0.001, np2 = 0.739, large effects). CS presented better results than NCS in YYIRT at both mid (mean difference: 84.4m, p = 0.040) and post-assessment (mean difference: 64.7m, p = 0.042). RSAmean was smaller under CS at mid (mean difference: -0.078 s, p = 0.012) and post-assessment (mean difference: -0.058s, p = 0.045). In conclusion, the results suggest that the CS condition leads to better YYIRT performance and reduced RSAmean compared to NCS. Practically, incorporating CS into training protocols for players who do not regularly participate in matches - such as unselected players or non-starters with limited playing time - may help maintain physical capacities, particularly endurance and repeated sprint ability, as these players are often exposed to lower physical demands during matches.